PENGARUH MANAJEMEN PROMOSI KESEHATAN DALAM MENINGKATKAN PENGETAHUAN KESEHATAN REPRODUKSI KADER POSYANDU DI DESA CIPANCUR KECAMATAN KALIMANGGIS KABUPATEN KUNINGAN - Ahmad Ropii; Suci Fitriana Pramudya Wardani (JOURNAL OF BAJA HEALTH SCIENCE, 2022)
Reproductive health is a health program that is currently receiving special attention, both globally and nationally. One of the causes of the high maternal mortality rate and infant mortality rate is the number of cases of early marriage. Immature reproductive organs in adolescent girls can be at risk for various diseases such as cervical cancer, breast cancer, myoma and uterine cancer. The number of cases of sexually transmitted diseases each year has increased significantly. The incidence of STIs in Indonesia tends to increase overall. “Gonorrhoea, Syphilis” was recorded in 2011 as many as 11,280. Of these cases, there were 5,131 (45.4%) gonorrhea cases, 4725 (41.8%) syphilis cases. In 2012 there were an increase of 13,043 cases distributed as many as 6003 (46.0%) cases of gonorrhea, 5216 (40.0%) cases of syphilis. This study aims to determine the effect of health promotion management in increasing knowledge of reproductive health of posyandu cadres in Cipancur Village, Kalimanggis District, Kuningan Regency.:This type of research is a quasi-experimental with a pre-test and post-test only design. The population is posyandu cadres of 20 people. The sampling technique used purposive sampling method in the posyandu cadre group in Cipancur Village. The instrument to measure in this study was a questionnaire that was given before and after counseling. Data analysis used paired t test with confidence = 0.05. Based on the results of the analysis of the paired t test, it shows that there is an influence of health promotion management in increasing the knowledge of reproductive health of posyandu cadres with p=0.000. Based on these results, it can be concluded that there is an effect of health promotion management before and after reproductive health counseling on increasing knowledge on reproductive health of posyandu cadres. Researchers suggest that each cadre can convey knowledge to other communities so that other people can feel the results obtained by the cadres.